Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/2000656x.2017.1330208
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors influencing drain amount, time to drain removal, and seroma formation in patients undergoing immediate expander-implant breast reconstruction

Abstract: The use of ADM and initial inflation ratio do not influence days to drain removal or seroma formation. A longer period of drain placement is expected when a larger expander is used or in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
3
15
1
Order By: Relevance
“…Recent studies have identified larger expander/implant size to be associated with increased reconstructive complications, 31,32 a finding that is in agreement with our data. A likely explanation for the increased complication rate is that larger expanders and implants put added pressure on already attenuated mastectomy skin flaps.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have identified larger expander/implant size to be associated with increased reconstructive complications, 31,32 a finding that is in agreement with our data. A likely explanation for the increased complication rate is that larger expanders and implants put added pressure on already attenuated mastectomy skin flaps.…”
Section: Discussionsupporting
confidence: 93%
“…14 It has been hypothesized that additional synthetic material might lead to a prolonged inflammatory response contributing to a longer drain time. 12 However, this could not be seen in the present material as daily drainage outputs and drain times were similar. Nonetheless, there were more seroma aspirations and significantly more seroma formation present during the exchange to permanent implants.…”
Section: Discussioncontrasting
confidence: 56%
“…This study compares seroma production in implant-based immediate breast reconstruction with a biological mesh with that of a synthetic mesh. Seroma formation is affected by patient-related factors, such as older age, higher BMI, and larger breast size (mastectomy weight), 6,12 by surgical factors, such as the size of TEs used and axillary lymph node dissection, 12,13 and by qualities of the mesh/matrix. The present study compares the right breast with left breast in the same patient, and the operations were performed in the same way, save the mesh/matrix used, in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…The avoidance of repeated aspirations could also help prevent additional unnecessary physical and psychological trauma and aspiration-related wound infection. [161718] Despite the promising results, however, this study was limited because it was a non-randomized retrospective study with a small sample. Detection and selection biases could not be avoided completely.…”
Section: Discussionmentioning
confidence: 99%